Meta-Humans and Metanoia: The Moral Dimension of Extraterrestrials - Kracher, Alfred (Zygon, 2006)
Abstract. Although we do not know whether intelligent extraterrestrials exist, they are a permanent fixture of literature and philosophical argument. Part of their appeal is that they watch us from above and thus serve as a metaphor for human self-reflexivity. This makes fictional aliens especially useful when moral issues are at stake. In order to evaluate stories about aliens with respect to moral conclusions two conditions must be fulfilled. First, the stories have to be detailed enough that we can understand the circumstances of the aliens' moral choices. Therefore science fiction often is more useful than arguments involving aliens in short technical papers. Second, their fictional lives need to be possible in our own universe, or very nearly so, in order to be relevant for our own moral conduct. Taking as an example the unfallen aliens in C. S. Lewis's novels Out of the Silent Planet (1938) and Perelandra (1943), we can acknowledge the theological interest and literary subtlety. Nonetheless, the stories fail as moral parables in one important respect: The aliens depicted could not be a product of evolution in our universe, at least as we currently understand its scientific laws. This realization has important consequences for our self-understanding and thus underlines how fictional aliens can be useful in making sense of the complexities involved in moral argumentation.